2015
DOI: 10.1002/job.2025
|View full text |Cite
|
Sign up to set email alerts
|

How to dissolve fixed-pie bias in negotiation? Social antecedents and the mediating effect of mental-model adjustment

Abstract: SummaryFixed-pie bias, defined as the erroneous belief that the other negotiation party's interest is directly opposite to one's own, has been a consistent hurdle that negotiators must overcome in their efforts to achieve optimal negotiation outcomes. In this study, we explore the underlying cognitive mechanism and the social antecedents of fixed-pie bias reduction in negotiation. Using data from a negotiation simulation with 256 participants, we found that mental-model adjustments made by negotiators could ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 89 publications
(201 reference statements)
0
6
0
Order By: Relevance
“…Existing research supports these hypotheses, with people who perceive lower corresponding interests behaving less cooperatively within a negotiation (e.g., Liu, Liu, & Zhang, 2016; Thompson, Valley, & Kramer, 1995). Recent work has also found that strategies that take into account the degree of corresponding interests in a situation are more successful at initiating and maintaining reciprocal relations relative to other strategies (Fischer et al, 2013).…”
Section: Interdependence Inferences and Cooperationmentioning
confidence: 98%
“…Existing research supports these hypotheses, with people who perceive lower corresponding interests behaving less cooperatively within a negotiation (e.g., Liu, Liu, & Zhang, 2016; Thompson, Valley, & Kramer, 1995). Recent work has also found that strategies that take into account the degree of corresponding interests in a situation are more successful at initiating and maintaining reciprocal relations relative to other strategies (Fischer et al, 2013).…”
Section: Interdependence Inferences and Cooperationmentioning
confidence: 98%
“…Our findings contribute to negotiation research by identifying a large-scale factor with major social implications predicting the extent to which people construe success in a zero-sum manner and their ability to realize integrative value generation potential in negotiations. Although the tendency to construe outcomes in a zero-sum manner is believed to be a major obstacle to value generation in negotiations, past work identified relatively few reasons why people exhibit this tendency, most notably culture (Gelfand & Christakopoulou, 1999), time pressure (De Dreu, 2003), emotions (Adam & Brett, 2015; Pietroni et al, 2008), mental models (Liu, Liu, & Zhang, 2016), and accountability (Peng et al, 2015). None of the antecedents identified in past work is systematically correlated with socioeconomic disadvantage, which is why zero-sum construal of success has so far not been considered as a factor relevant to social justice, mobility, and equality of opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…A negotiation frame may invoke a fixed‐pie bias. Liu, Liu, and Zhang (2015) found that mental model adjustments (updated analysis and understanding of the negotiation) decrease the bias whereas accountability to an ingroup increases it. Interestingly, multiparty negotiators have weaker fixed‐pie biases than dyadic negotiators.…”
Section: Issue Framingmentioning
confidence: 99%